Development of Illustrated Storybooks as a Learning Medium to Enhance Students' Reading Interest - Latifa, Gusti; Suzanne, Nina; Zulhendri, Zulhendri (Journal of Islamic Education Students (JIES), 2023)
An important component of elementary school students' academic growth is their enthusiasm for reading, especially in the lower grades. The purpose of this study is to examine students' demands for illustrated storybooks, confirm the accuracy of the created books, gauge how useful they are for piqueing children's interest in reading, and measure the effects of utilizing these books in the classroom. This study uses a research and development methodology to gather both quantitative and qualitative data. The four steps of the research process define, design, develop, and disseminate are guided by the 4D model. The results of this study support the usefulness of employing illustrated storybooks to increase pupils' enthusiasm for reading. The storybooks are suitable to satisfy the demands of the pupils thanks to the creation and validation procedures. The storybooks' ability to encourage reading engagement among primary school pupils is shown by the favorable response from instructors and students regarding the usefulness of the books. This study makes a contribution to the field of education by offering instructors insightful information and a useful tool to raise their students' motivation for reading and general literacy ability.